Numerical analysis of stability of the stiffened plates subjected aliquant critical loads - Gaik A. Manuylov; Sergey B. Kositsyn; Irina E. Grudtsyna (Structural Mechanics of Engineering Constructions and Buildings, 2020)
The aim of the work is to research the precritical and postcritical equilibrium of the stiffened plates subjected aliquant critical loads. Methods. The finiteelement complex MSC PATRAN - NASTRAN was used in the paper. To simulate the plates, flat four-node elements were used. Calculations taking into account geometric nonlinearity were carried out. The material of the shells was considered absolutely elastic. Results. A technique has been developed to study the stability of reinforced longitudinally compressed plates; the critical forces of the stiffened plates of various thicknesses had been calculated. Graphs of deflections dependences on the value of the compressive load had been constructed. The influence of initial geometric imperfections on the value of the critical loads for stiffened plates has been investigated.